Identifying Risk Factors of Patients with Ulcerative Colitis - Ramlah M. M. Al karaawi; Jihad Jawad Kadhim (Kufa Journal for Nursing Sciences)
Background׃ Ulcerative colitis a lifelong inflammatory illness is marked by persistent inflammation of the mucosal surface that begins in the rectum and spreads toward the influence of a portion or the entire colon, the disease has different periods from severity or exacerbation to remission.